Analysis of local community ecological knowledge on mangrove ecotourism development in Donggala Regency, Central Sulawesi, Indonesia - Trianto, Manap; Adnan, Bahana Aditya (Interdisciplinary International Journal of Conservation and Culture, 2024)
The mangrove area in Donggala Regency is a unique and potential area, but the area tends to be threatened by increasing mining activities in the area. Management of the mangrove area in Donggala Regency as an ecotourism area is an alternative form as an innovative effort to maintain environmental functions as a provider of environmental services in order to remain sustainable. This study was aimed at analyzing the Local Community Ecological Knowledge (LCEK) pertaining to mangrove ecosystems and ecotourism development in Donggala Regency. The study used a survey method, utilizing the analysis of the tourism suitability index (IKW) and the carrying capacity of the area (DDK). Community knowledge and perceptions were based on a Likert scale scoring system. The results of the study and the discussion showed that people in Donggala Regency had local ecological knowledge of mangrove forests, especially mangrove habitats, mangrove damage factors and the impact of mangrove damage was better than the function of mangroves. Utilization of mangrove ecosystems in Donggala Regency is very diverse, ranging from the utilization of mangrove stems, fruits, leaves and roots and fishery products such as small fish and shellfish. The community's understanding of ecotourism activities was very good and they agreed with the ecotourism activities that were carried out.